2017
DOI: 10.1111/apha.12912
|View full text |Cite
|
Sign up to set email alerts
|

Control of breathing and ventilatory acclimatization to hypoxia in deer mice native to high altitudes

Abstract: Our results suggest that highland deer mice have evolved high rates of alveolar ventilation and respiratory O uptake without the significant enlargement of the carotid bodies that is typical of VAH in lowlanders, possibly to adjust the hypoxic chemoreflex for life in high-altitude hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
88
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 75 publications
4
88
1
Order By: Relevance
“…We measured the ventilatory and metabolic responses to acute hypoxia using plethysmography and respirometry techniques similar to those used previously for mole-rats and other small mammals. 22,[35][36][37] Mole-rats were individually placed, unrestrained, inside a 1 L (C.h.m., C.h.p., C.h.h., F.d., G.c. and H.e.)…”
Section: Acute Hypoxia Responsesmentioning
confidence: 99%
“…We measured the ventilatory and metabolic responses to acute hypoxia using plethysmography and respirometry techniques similar to those used previously for mole-rats and other small mammals. 22,[35][36][37] Mole-rats were individually placed, unrestrained, inside a 1 L (C.h.m., C.h.p., C.h.h., F.d., G.c. and H.e.)…”
Section: Acute Hypoxia Responsesmentioning
confidence: 99%
“…In the respiratory system, Ivy et al, in deer mice, observed high alveolar ventilation and oxygen uptake rates without changes in the carotid bodies, which in lowlanders adjust the hypoxic chemoreflex to high altitude hypoxia. Barna et al investigated the role of purinergic receptors in central breathing control, while a number of excellent studies have recently taken a closer look at pulmonary vascular wave dynamics, vasomotor function and vessel wall architecture and dynamics .…”
mentioning
confidence: 99%
“…In the present issue, Ivy et al . begin to explore the mechanisms underlying these evolved differences in the control of breathing.…”
mentioning
confidence: 99%
“…The F1 progeny of each population were raised to adulthood under identical low altitude conditions and then were acclimated to normoxia or hypobaric hypoxia (12 kPa, simulating hypoxia at ~4300 m) for 5 months. Ivy et al . then recorded the effects of stepwise reductions in inspired O 2 on ventilation, respiratory water loss, heart rate, arterial O 2 saturation, metabolism and growth of the carotid body.…”
mentioning
confidence: 99%
See 1 more Smart Citation